Benthic algal mats of some lakes of Inexpressible Island (northern Victoria Land, Antarctica) - FUMANTI, Bruno; ALFINITO, Silvia; Paolo Cavacini (Polar Biology, 1997)
Benthic algal mats from four lakes located on Inexpressible Island (northern Victoria Land, Antarctica) were studied, analysing their structure and Aoristic composition. Thirty taxa of algae were identified: 11 Cyanophyta, 15 Bacillariophyta and 4 Chlorophyta. The lake mats contained from 15 (lake C) to 26 species (lake D). The number of diatom frustules in the mats varied from 771 x 10(3) (lake C) to 9428 x 10(3) frustules g(-1) (lake B). In terms of floristic composition and macromorphology, these mats were observed to be very similar to moat mats described from Lake Gondwana (northern Victoria Land) and the Dry Valleys lakes of southern Victoria Land.